Nostalgia and its relationship to compulsive hoarding in women (a proposed program for behavior modification( (Journal of the College of Basic Education, 2025)
The problem of the research and its importance fall within the innate tendency of the human being, which is nostalgia for the past and glorifying it in a theological way, although it meant to him at the time a time of much pain and bitter reality. Over time, its meaning changed and became a beautiful reality due to life experiences that depend greatly on the psychological time that a person feels subjectively. Buss launched in his theory of the sense of self, which is the theory adopted for the current research, on Nostligia for the past and nostalgia. Nostalgia is a state of self-reflection and introspection of the private self, distant or close to the public self and the social self that may come close to each other, which is called the extended self. It is a syndrome of behavior, negatively and positively, with time and behavior according to its moral value that is formed in him according to some psychological facts and illusions that give him certain meanings that may push him to adopt bad behaviors and habits such as compulsive Hoarding of old things and keeping them, which is tinged with an emotional tendency, which is the trait of pathological attachment, and among its most prominent symptoms are: Holding on to worthless things to the point of sacrificing everything he owns to keep them and having an obsessive belief that he will need them one day and his anger is aroused as soon as someone thinks of approaching or getting rid of them and it may negatively affect his personal and family life as it may take up space and cause harassment to family members and may provoke angry behavior in them and lead to family disputes that may lead to murder. A measurement tool was prepared for the current research according to a scientific methodology for psychological and educational measurements and extracting the apparent validity of the scale by presenting it to (10) arbitrators, and extracting the stability by the method of splitting the half and the discriminating power of the paragraphs. All paragraphs of the two scales were prepared distinctive and have high validity and stability. Below are the results. - The elderly suffer from Nostligia (longing for the past) and Compulsive Hoarding to varying degrees of severity, and this indicates that the elderly tend to grow towards the past- The future and neglect of the present. We can conclude from this that the elderly prefer a simple life over a life of technological development that the world has witnessed, considering that life was less complicated than it is now. There is also a correlation between nostalgia and Compulsive Hoarding among the elderly. The research came out with a number of recommendations and proposals, including: Taking the elderly to places that remind them of the old landmarks in which they used to live, such as villages and suburbs, to create a state of communication between past and present life. - Rehabilitating individuals who tend to Compulsive Hoarding to change their temporal orientations towards the present to feel their authentic existential presence.